Effectiveness of Helicobacter pylori eradication in the prevention of primary gastric cancer in healthy asymptomatic people: A systematic review and meta-analysis comparing risk ratio with risk difference. - Takeshi Seta; Yoshimitsu Takahashi; Yoshinori Noguchi; Satoru Shikata; Tatsuya Sakai; Kyoko Sakai; Yukitaka Yamashita; Takeo Nakayama (PLoS ONE, 2017)
Background Helicobacter pylori infection is strongly associated with gastric cancer occurrence. However, it is unclear whether eradication therapy reduces the risk of gastric cancer occurrence. We evaluated whether H. pylori eradication reduces the risk of primary gastric cancer by using both risk ratio (RR) and risk difference (RD). Methods Searches of PubMed, EMBASE, Google scholar, the Cochrane Library, and the Japan Medical Abstracts Society as well as those registered in databases of the Cochrane Central Register of Controlled Trials, metaRegister of Controlled Trials, ClinicalTrials.gov, controlled-trials.com, UMIN-CTR, JMACCT-CTR, and JAPIC-CTI between January 1965 and March 2017, supplemented with manual screening. Randomized controlled trials (RCTs) in which eradication therapy were implemented for the interventional group but not for the control group, and assessed the subsequent occurrence of primary gastric cancer as the main outcome. Two authors independently reviewed articles and extracted data. Integrated results for all data were presented as RR and RD. Results Seven studies met inclusion criteria. The reductions in risk of primary gastric cancer occurrence in terms of overall RR and RD were 0.67 (95% CI: 0.48 to 0.95) and -0.00 ([95% CI: -0.01 to 0.00]; number needed to treat: 125.5 [95% CI: 70.0 to 800.9]), respectively. Conclusions The effectiveness of H. pylori eradication therapy in suppressing the occurrence of primary gastric cancer was significant and comparable to that of previous studies in terms of the estimated RR. However, the estimated RD was slight and not statistically significant.